Experimental and numerical study of self-sustaining fluid films generated in highly compressible porous layers imbibed with liquids. (November 2020) - Kunik, Serguei; Fatu, Aurelian; Bouyer, Jean; Doumalin, Pascal
Abstract: Ex-poro-hydrodynamic (XPHD) lubrication is a biomimetic-inspired lubrication mechanism consisting of self-sustained fluid films generated within highly compressible porous layers imbibed with liquids, whose solid phase induces compressive elastic forces that are negligible compared to the hydrodynamic forces generated inside the porous medium. This work focuses on the performance of XPHD lubrication in the context of tangential movement, adapted to the case of thrust bearings at low and medium rotational speeds. An in-depth study of a pre-selected porous material (polyurethane foam) was carried out in order to determine the physical characteristics and the crucial parameters for XPHD lubrication, namely the porosity and the permeability. The paper also proposes a theoretical and numerical model of XPHD lubrication. Classical lubrication assumptions are used, and flow within the porous medium is predicted using a new form of the Reynolds equation. A specially developed test rig allows for an experimental study of the XPHD lubrication mechanism. Finally, a comparison of the modeling and experimental results is presented.